A new combination in Cremanthodium (Asteraceae, Senecioneae) from Sichuan, China - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2016)
Critical examination of herbarium specimens (including type material) of Cremanthodium ellisii var. roseum (Asteraceae, Senecioneae) has shown that the variety should be transferred to C. brunneopilosum. We therefore propose a new combination, C. brunneopilosum var. roseum.